(untitled) (Conference on English Language Teaching, 2023)
Technology has been used more and more into educational environments in recent years. Teachers have been utilizing technology to enrich classroom activities and promote student learning. One of the ways in which teachers have incorporated technology is through the use of online games. Online games have been found to increase student interest and motivation, making education more interactive and enjoyable. This paper explores the most popular online games used for education and its impact for the learning achievement. A survey on literatures was conducted to obtain the data. The top 5 online educational games were overviewed in this paper. They were selected based on the number of articles mentioning these games and their effectiveness in promoting the English as Foreign Language (EFL) learning. Considering the benefits of online games for educational context, educators are challenged to be more creative, innovative and adaptive toward the advance technology and its application to enrich the EFL practice.